Culture and development cultural patterns in areas of uneven development - Alexander, Kanjirathara Chandy 1935-; Kumaran, K. P. 1955-.; National Institute of Rural Development (India). (New Delhi Sage Publications, 1992)
Impact of development programs on cultural values; study with special references to Kerala and Uttar Pradesh, India.
Copyright: National Institute of Rural Development.
Includes bibliographical references (p. [202]-203).
Keywords: Rural development -- India -- Kerala; Rural development -- India -- Uttar Pradesh; Social change -- India -- Kerala; Social change -- India -- Uttar Pradesh; Kerala (India) -- Social conditions; Uttar Pradesh (India) -- Social conditions